Occurrence and variability of iodinated trihalomethanes concentrations within two drinking-water distribution networks - Ioannou, Panagiotis; Charisiadis, Pantelis; Andra, Syam S.; Makris, Konstantinos C. (My University, 2016)
Non-iodo-containing trihalomethanes (TTHM) are frequently detected in chlorinated tap water and currently regulated against their carcinogenic potential. Iodinated THM (ITHM) may also form in disinfected with chlorine waters that are high in iodine content, but little is known about their magnitude and variability within the drinking-water pipe distribution network of urban areas. The main objective of this study was to determine the magnitude and variability of ITHM and TTHM levels and their corresponding daily intake estimates within the drinking water distribution systems of Limassol and Nicosia cities of Cyprus, using tap samples collected from individual households (n=37). In Limassol, mean household tap water ITHM and TTHM levels was 0.58 and 38μgL-1, respectively. Dichloroiodomethane (DCIM) was the dominant species of the two measured ITHM compounds accounting for 77% of total ITHM and in the range of 0.032 and 1.65μgL-1. The range of DCIM concentrations in Nicosia tap water samples was narrower (0.032 - 0.848μgL-1). Mean total iodine concentration in tap water samples from the seaside city of Limassol was 15μgL-1 and approximately twice to those observed in samples from the mainland Nicosia city. However, iodine concentrations did not correlate with the ITHM levels. The calculated chronic daily intake rates of ITHM were low when compared with those of TTHM, but because of their widespread occurrence in tap water and their enhanced mammalian cell toxicity, additional research is warranted to assess the magnitude and variability of human ITHM exposures.
Keywords: Bromine; Chlorine; Distribution system; Drinking-water; Iodine; Trihalomethanes; Urban